The Internet (Basic reference from A to Z) - Falk, Bennett (Singapore : Tech Publications Pte Ltd, 1995)
This book introduces the basics of working with the Internet, primarily for people who will connect to the Internet by phone. You'll learn what the Internet is and how to use it from your computer. Along the way, some key information resources will be introduced as starting points for exploring the Internet. You'll soon find that the Internet doesn't stand still, but the topics covered here will give you everything you need to get started with the Internet as it is now and to grow with it as new application and resources are introduced.
Introduction -- Part One. Introducing the Internet -- Part Two. First-Generation Internet Application: ftp, telnet, and E-Mail -- Part Three. The Internet Community's Applications -- Appendices.
Includes bibliographical references and index.
Keywords: INTERNET (COMPUTER NETWORK)